Attractiveness of Loyalty Programs for Consumers of Tourism Services (Laisvalaikio tyrimai, 2018)
Research background. In order to enhance the company's competitiveness and efficiency, there is a strong focus on customers’ loyalty formation by using a variety of loyalty programs, which not only help to retain existing customers but also to attract the new ones. Loyalty programs are widely used in various business sectors by investing finances, material, human and time resources, developing customer habits, behavioural analysis, IT, filing, and data storage applications. Actually loyalty programs work in many spheres of activity and organizations can feel the economic benefits of it. No exception is the tourism sector where the clients have recently become very price sensitive because tourism services have changed. However, the main question is if they are effective. Such studies have not been conducted in Lithuania (tourism enterprises itself analyse programs for attractiveness of tourism services to consumers and at the same time see the benefit for the organization). The aim of the research was to find out whether the loyalty programs of tourism sector are attractive to consumers of tourism services. This paper analyses the concept of loyalty programs and their attractiveness to consumers of tourism services. The definitions (found in literature) of loyalty programs allow to classify them into two groups where the first group emphasizes the added value and benefits of the development and the second one – increasing loyalty of customers. Research methods. An empirical study (questionnaire survey) was made in summer of 2013 with 413 participants, also the literature material was applied. Research results showed that the users of tourism service, regardless of their age, appreciated loyalty programs applied in the tourism market. The most recognized short-term loyalty promotion means are gifts and prizes, as they provide a good luck by switching, improve mood, cheer. They can influence a person’s choice of the tourism business and encourage to purchase. Respondents also expect a special price, lower price, and higher quality of services. However, Loyalty programs which require more time and bigger involvement, and participation are in form of contest or point accumulation programs are valued by customers as less attractive. To sum up, it can be said that loyalty programs is an effective tool in tourism markets in Lithuania. Keywords: loyalty, loyalty program, tourism.